Pengaruh Konservatisme Akuntansi, Investment Opportunity Set, dan faktor lainnya terhadap Kualitas Laba - Riztia Maulia; Irwanto Handojo (Jurnal Bisnis dan Akuntansi, 2022)
This study aims to obtain empirical evidence and analyze factors that affect earnings quality. The independent variables in this study are institutional ownership, independent commissioner, accounting conservatism, investment opportunity set, capital structure, and company size. Meanwhile the dependent variable in this study is earnings quality. The company used in this research manufacturing companies that listed on the Indonesian Stock Exchange (IDX) from 2018 to 2020. This research using purposive sampling method where there are 376 company year data. This research using multiple regression method to examine the effect of independent variables and dependent variable earnings quality. The result of this study show that accounting conservatism and company size has an effect on earnings quality. Meanwhile institutional ownership, independent commissioner, investment opportunity set and capital structure has no effect on earnings quality.